2021
DOI: 10.1002/ece3.7291
|View full text |Cite
|
Sign up to set email alerts
|

Measuring temporal patterns in ecology: The case of mast seeding

Abstract: How to accurately describe temporal patterns in ecological processes has been a long-standing question in ecology (McCann, 2000).Metrics to estimate stability, temporal variability, and resilience are, actually, still under intense debate (Arnoldi et al., 2016). The field of masting, for which assessing temporal patterns of seed production is crucial, is not an exception. Mast seeding, or masting, has traditionally been described as a reproductive phenomenon consisting of the highly variable and synchronized p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…However, caution should be exercised in interpreting the confidence intervals because this approach assumes a normal distribution of CV values. The CV can be a useful metric for temporal variability when there are no zero values and the specific chronological sequence is not of interest ( Fernández-Martínez and Peñuelas 2021 ). Note that the CV as calculated here represents a population-level estimate of the variability in the means of the phenotypic traits among years ( Herrera 1998 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, caution should be exercised in interpreting the confidence intervals because this approach assumes a normal distribution of CV values. The CV can be a useful metric for temporal variability when there are no zero values and the specific chronological sequence is not of interest ( Fernández-Martínez and Peñuelas 2021 ). Note that the CV as calculated here represents a population-level estimate of the variability in the means of the phenotypic traits among years ( Herrera 1998 ).…”
Section: Methodsmentioning
confidence: 99%
“…Among-year variability in plant reproduction follows a continuous gradient, so using dichotomous classifications such as 'masting' and 'non-masting' can be problematic (Herrera et al 1998;Koenig and Knops 2000;Fernández-Martínez and Pe˜ 2021). This was recently demonstrated nuelas by Pearse et al's (2020) global analysis of mean CVps of 311 species, where the dataset showed a unimodal continuous distribution of CVps ranging from 0.5 to 3.3 (Fig.…”
Section: Quantifying Mastingmentioning
confidence: 93%
“…Understanding the variation in masting at different organizational levels is a fundamental aspect of the discipline. Yet, the methods used to measure masting–masting metrics – continue to be controversial (Crone et al ., 2011; Fernández‐Martínez & Peñuelas, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The metrics termed volatility and periodicity provide a way to compare time‐series variation between trees, allowing scaling‐up to populations, and species (Qiu et al ., 2023). The term volatility was introduced to distinguish it from terms related to variability or variance (such as CV or lag‐1 approaches; Fernández‐Martínez & Peñuelas, 2021). Volatility measures variation in the frequency domain with a focus on the biologically significant long intervals.…”
Section: Introductionmentioning
confidence: 99%